2019 Guideline for Management of Wounds in Patients With Lower-Extremity Venous Disease (LEVD): An Executive Summary. Issue 2 (March 2020) - Kelechi, Teresa J.; Brunette, Glenda; Bonham, Phyllis A.; Crestodina, Lea; Droste, Linda R.; Ratliff, Catherine R.; Varnado, Myra F.
Abstract : This article provides an executive summary of the 2019 Guideline for Management of Wounds in Patients with Lower-Extremity Venous Disease (LEVD) published by the Wound, Ostomy and Continence Nurses Society (WOCN). The executive summary presents an overview of the systematic process used to update and develop the guideline. It also lists the specific recommendations from the guideline for assessment, prevention, and management of LEVD and venous leg ulcers (VLUs). In addition, the guideline includes a new section regarding implementation of clinical practice guidelines. The LEVD guideline is a resource for WOC nurse specialists and other nurses, physicians, therapists, and health care professionals who work with adults who have or who are at risk for VLU. Abstract : Supplemental Digital Content is Available in the Text.